GROWTH CHARACTERISTICS AND YIELD OF DAI THOM 8 RICE VARIETY IN WINTER-SPRING CROP 2017–2018 IN THUA THIEN HUE - Vũ, Nguyễn Quang Hoàng; Hồng, Hoàng Thị Kim (Hue University Journal of Science: Natural Science, 2018)
This study aims to evaluate the growth characteristics, yield, and adaptability to local natural conditions of the Dai Thom 8 rice variety in the Winter-Spring crop 2017–2018. The variety was cultured at Mong An village, Phu My, Phu Vang, Thua Thien Hue. Rice variety Dai Thom 8 had a germination rate of 92.02% ± 0.83%, growth duration of 117 days ± 0.72 days, and plant height of 90.98 cm ± 3.65 cm. The biological yield was 11.843 ton/ha ± 1.428 ton/ha, and the grain yield was 6.565 ton/ha ± 0.149 ton/ha. This rice variety had a better adaptability, growth, and development compared with Khang Dan 18 variety as a control. These results could serve as the scientific basis for the cultivation of this potential rice variety in many rice growing areas of the province. This rice variety could also be used to replace the degrading varieties of the locality. At the same time, this variety could be added to the cultivation structure as one with a high yield and a capability of growing in the natural conditions of Thua Thien Hue province.